Penyuluhan Hukum Tindak Pidana Narkotika di Desa Sindangagung Kecamatan Sindangagung Kabupaten Kuningan - Hidayat, Sarip; Bachtiar, Beben Muhammad; Yuhandra, Erga; Rifa’i, Iman Jalaludin; Dialog, Bias Lintang; Adhyaksa, Gios; Anugrah, Dikha; Nurmayanti, Andini; Lestari, Dewi (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2024)
Ratified Law No. 35 of 2009 concerning​ Narcotics in Indonesia, Law the expected capable cope problem Act Criminal narcotics and precursors narcotics from various aspect, so Can reduce reduction of illegal supply and demand for save Indonesian people from threat narcotics. Research methods used​ in counseling This that is stage hearing, implementation and evaluation report, results and discussion This that is effort prevention follow criminal narcotics must done in a way comprehensive, and must be remove that stigma circulation narcotics No a must problem done government just but This is a must problem solved by everyone so that it doesn't happen Act Criminal Narcotics, as base the law that is Constitution Number 35 of 2009 concerning narcotics.